2019
DOI: 10.1145/3369392
|View full text |Cite
|
Sign up to set email alerts
|

Multisensor Adaptive Control System for IoT-Empowered Smart Lighting with Oblivious Mobile Sensors

Abstract: The Internet-of-Things (IoT) has engendered a new paradigm of integrated sensing and actuation systems for intelligent monitoring and control of smart homes and buildings. One viable manifestation is that of IoT-empowered smart lighting systems, which rely on the interplay between smart light bulbs (equipped with controllable LED devices and wireless connectivity) and mobile sensors (possibly embedded in users’ wearable devices such as smart watches, spectacles, and gadgets) to provide automated illuminance co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a separate study, Goudjil et al 8 introduced a straightforward and economical control scheme for managing the color temperature or ambiance of lighting in a room, demonstrating good performance. Areg Karapetyan et al 9 suggested leveraging IoT technology to adjust light brightness, color intensity, and energy consumption based on work requirements for efficient adaptive control. Intelligent remote-controlled ceiling lights, a recent innovation in smart home technology, are equipped with networking capabilities for remote control through smartphone apps, voice assistants, or other smart home systems.…”
Section: Related Workmentioning
confidence: 99%
“…In a separate study, Goudjil et al 8 introduced a straightforward and economical control scheme for managing the color temperature or ambiance of lighting in a room, demonstrating good performance. Areg Karapetyan et al 9 suggested leveraging IoT technology to adjust light brightness, color intensity, and energy consumption based on work requirements for efficient adaptive control. Intelligent remote-controlled ceiling lights, a recent innovation in smart home technology, are equipped with networking capabilities for remote control through smartphone apps, voice assistants, or other smart home systems.…”
Section: Related Workmentioning
confidence: 99%
“…Ayaz et al proposed the plan and execution of another savvy sunshine-based lighting control framework to furnish energy reserve funds in open structures with ordinary lighting frameworks [2]. Karapetyan et al studied that the Internet of ings (IoT) brings a new paradigm of integrated sensing and actuation systems for intelligent monitoring and control of smart homes and buildings [3]. Mahbub et al centered around the plan and execution of an insightful independent lighting and ventilation framework that empowers energy-mindful independent lighting, observing temperature, mugginess, carbon dioxide (CO 2 ) fixation, and exhaust cloud [4].…”
Section: Related Workmentioning
confidence: 99%